1996
DOI: 10.1080/00223980.1996.9914985
|View full text |Cite
|
Sign up to set email alerts
|

Religiosity, Gender, and the Double Standard

Abstract: Scottish teenagers (N = 690) participated in a survey concerning the relationship between religiosity, gender, and social judgments of sexual activity. Respondents estimated the number of sexual partners of 20-year old men and women and made evaluative judgments of sexually active men and women on positive and negative dimensions. On both tasks, evidence was obtained for the operation of a double standard. Women were expected to have fewer sexual partners than men, and their sexual activity was judged more neg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 15 publications
0
22
0
1
Order By: Relevance
“…For example, if a study explicitly requires participants to rate the appropriateness of certain sexual behaviors for men, immediately followed by identical questions regarding women (e.g., Ferrel, Tolone, & Walsh, 1977;Sheeran, Spears, Abraham, & Abrams, 1996;Sprecher & Hatfield, 1996), participants may try to answer either in an egalitarian manner or in a manner that is consistent with what they believe to be the norm. Given that many people have preconceived notions about the sexual double standard (Milhausen & Herold, 1999, it is important to minimize demand characteristics when researching attitudes toward sexuality.…”
Section: Sexual Double Standard Research Methodologymentioning
confidence: 99%
“…For example, if a study explicitly requires participants to rate the appropriateness of certain sexual behaviors for men, immediately followed by identical questions regarding women (e.g., Ferrel, Tolone, & Walsh, 1977;Sheeran, Spears, Abraham, & Abrams, 1996;Sprecher & Hatfield, 1996), participants may try to answer either in an egalitarian manner or in a manner that is consistent with what they believe to be the norm. Given that many people have preconceived notions about the sexual double standard (Milhausen & Herold, 1999, it is important to minimize demand characteristics when researching attitudes toward sexuality.…”
Section: Sexual Double Standard Research Methodologymentioning
confidence: 99%
“…However, similar negative attributions are not made about sexually promiscuous males. For example, a study of Scottish teenagers found that sexually active women were perceived as less popular, as having less self-respect, and as more irresponsible than sexually active men (Sheeran et al 1996). A similar study of college students in the United States found that men believed it was more acceptable for men to have sexual relations on a first date than it was for women (Sprecher and Hatfield 1996).…”
Section: Sexual Promiscuitymentioning
confidence: 96%
“…For example, males tend to report being more permissive and more sexually active than females. Furthermore, the differences between gender attitudes toward sexuality are impacted by religiosity: compared to religious men, religious women have more negative attitudes toward sexually active people, but this gender difference is not present for non-religious people (Sheeran et al 1996). This body of research implies that different attitudes toward sexuality may be impacted by both gender and religiosity.…”
Section: Studymentioning
confidence: 96%